Endovascular Therapy for Distal Superior Mesenteric Artery Mycotic Aneurysms due to Infective Endocarditis. (December 2019) - Higashiura, Wataru; Takara, Hiroaki; Kitamura, Ryoichi; Iraha, Tomotaka; Nakasu, Akio; Ishimine, Tohru; Yasutani, Tadashi; Wake, Minoru; Tengan, Toshiho
Purpose: To report 3 patients with infective endocarditis who underwent transcatheter arterial embolization for mycotic aneurysm of the distal superior mesenteric artery (SMA).Case Report: Three men (60, 64, and 65 years old) were diagnosed with infective endocarditis. Antibiotics were initiated immediately after admission and continued for several weeks to months. Distal SMA mycotic aneurysm was identified on computed tomography in the vicinity of the ileocolic artery at 33, 26, and 30 days after admission. In case 1, the ileal artery was occluded distal to the aneurysm, with collateral flow to the ileum. In case 2, the mycotic aneurysm was located below the ileocolic artery, which was stenosed distal to the lesion. In case 3, the aneurysm was located on a branch of the ileal artery. Transarterial embolization using microcoils was successfully performed in all patients. No complications associated with embolotherapy or relapse of infection were observed in these 3 patients at 60, 30, and 15 months, respectively.Conclusion: Transcatheter arterial embolization for distal SMA mycotic aneurysm could provide an alternative to open surgery. Anatomical assessment of collateral flow and preprocedure long-term antibiotic therapy could play important roles in preventing bowel ischemia and minimizing the risk of infection relapse.